Pengaruh Pendidikan Kesehatan Terhadap Pengetahuan Remaja Putri Kelas IX Tentang Kekerasan Seksual Di MTS Plus Roudhotul Muhibbin Kabupaten Bekasi Tahun 2023 - Siti Rohimah; Yulianti Yulianti (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
The Ministry of Women's Empowerment and Child Protection (PPPA) noted that as many as 25,050 women became victims of sexual violence in Indonesia throughout 2022. West Java is the region with the highest number of cases of violence against children and women in Indonesia. The Bekasi Regency Government, through the Women's Empowerment and Child Protection Service (DP3A), continues to strive to reduce cases of violence against children by providing outreach and education to the community. The aim of this research is to identify the influence of health education on teenagers' knowledge about sexual violence at MTS Plus Roudhotul Muhibbin Bekasi Regency in 2023. The research method used was the Quasi-experimental Pretest-Post Test With Control Group Design method. Sampling was taken with a total sampling of 59 people. Data analysis used frequency distribution and Wilcoxon test. This research carried out an intervention in the form of health education and evaluated it in a questionnaire. Data collection was carried out in November 2023 at MTS Plus Roudhotul Muhibbin, Bekasi Regency. The Wilcoxon test results in the intervention group obtained a p value of 0.000 < 0.05. The conclusion was that Ha was accepted or Ho was rejected, meaning that there was a significant influence on the provision of health education on teenagers' knowledge about sexual violence in the intervention group. Meanwhile, the control group got a p value of 0.102 > 0.05. The conclusion was that Ha was rejected or Ho was accepted, meaning there was no significant influence on the provision of health education on teenagers' knowledge about sexual violence in the Control group at MTs. Plus Roudhotul Muhibbin Bekasi in 2023. The results of the bivariate analysis showed that in the intervention group all respondents or 30 people (100%) experienced an increase in knowledge, while in the control group only 5 people (17.24%) experienced an increase in knowledge.It is hoped that the results of this research can increase teenagers' knowledge and be used as a reference for increasing knowledge and intensive approaches for teachers and health workers.